Numerical study on CTF code to predict void fraction in PWR sub channel conditions - Hoang , Minh Giang; Hoang , Tan Hung; Nguyen , Phu Khanh (Nuclear Science and Technology, 2015)
CTF is a version of the widely used COBRA-TF code with capability of 3D simulation for core sub channel thermal hydraulics behavior. Recently, CTF is reviewed and the consideration of CTF to predict void fraction in PWR sub channel conditions such as subcooled region still need more investigation. Due to the fact that the Chen’s correlation of heat transfer coefficient is developed for relatively low pressure and high quality conditions associated with forced convection vaporization, and is not strictly valid for PWR operation conditions, so that, in this study, some runs of single channel in the benchmark based on NUPEC PWR Sub channel and Bundle Tests (PSBT) are used to investigate void fraction prediction by CTF in subcooled region and also to verify some remarkable notice of CTF from other authors. The goal of the study is to evaluate deviation for CTF void fraction prediction in PWR sub channel conditions.